PENGARUH ACTUAL OR OBJECTIVE QUALITY, PRODUCT-BASED QUALITY, DAN MANUFACTURING QUALITY TERHADAP KEPUTUSAN PEMBELIAN PRODUK MOBIL DAIHATSU XENIA - Hendra Sastrawinata (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2012)
The research objective to be achieved in this study to analyze the effect of perceived quality of the product purchase decision Daihatsu Xenia.Ruang scope of this research is limited to the actual variables or objective quality, product-based quality, and manufacturing quality, then the dependent variable is the decision purchase. Actual variables simultaneously or objective Quality, variable based Product Quality, and Manufacturing Quality variables have a significant influence on purchase decisions Daihatsu Xenia acceptable. Demonstrated a significant influence of the value of F ratio of 50,719 based on the F test with R-square value of 0.613 (61.3%). While the remaining 38.7% is explained by other variables outside the model. Based on the results of testing the partial l (t test), unity hypothesis (H1) in this study which states that the actual or objective quality variables significantly influence purchasing decisions Daihatsu Xenia rejected. Based on the results of statistical tests obtained value t = 0867 and p = 0338 (p> 0.05) so that the unity hypothesis (H1) is rejected. The results of testing the second hypothesis (H2) in this study which states that the variable product based quality significantly influence purchasing decisions Daihatsu Xenia received. Based on the results of statistical tests obtained value t-count = 5575 and p = 0.000 (p